The Principle of Maslahah in Marriage Registration Policy: Preventing the Exploitation of Women and Children in Mandailing Natal Regency - Andri Muda Nst; Asrul Hamid; Raja Ritonga; Zuhdi Hsb; Ilham Ramadan Siregar (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2025)
The phenomenon of unregistered marriages in Mandailing Natal Regency remains a serious issue that weakens legal protection for women and children and increases the risk of exploitation of these vulnerable groups. This study aims to analyze the implementation of the maslahah principle in marriage registration policies and evaluate their effectiveness in preventing the exploitation of women and children. This research employs a qualitative method with a descriptive-analytical approach to explain the application of the maslahah principle in marriage registration and its relevance in exploitation prevention. The study location was selected purposively due to the high incidence of unregistered marriages and child marriage in Mandailing Natal Regency, as well as the strong influence of local cultural practices. A normative-empirical approach was applied by integrating the analysis of maslahah principles in Islamic law with the social realities within the community. Primary data were obtained through in-depth interviews with religious leaders, community leaders, and affected residents using purposive sampling, while secondary data were collected from literature and official documents. Data were gathered through interviews and observation, then analyzed qualitatively through data reduction, data display, and conclusion drawing, supported by source triangulation to ensure data validity. The results show that low legal awareness, perceptions that marriage registration is merely administrative, limited access to services, economic constraints, and widespread child marriage are key factors contributing to the high rate of unregistered marriages. The novelty of this research lies in the comprehensive integration of the maslahah principle with local empirical findings, producing a maslahat-based policy recommendation through legal education, expanded service access, and digital innovation as preventive measures to protect women and children. Fenomena pernikahan tidak tercatat di Kabupaten Mandailing Natal masih menjadi persoalan serius yang melemahkan perlindungan hukum bagi perempuan dan anak serta meningkatkan risiko eksploitasi terhadap kelompok rentan tersebut. Penelitian ini bertujuan untuk menganalisis implementasi prinsip maslahat dalam kebijakan pencatatan pernikahan serta mengevaluasi efektivitasnya dalam mencegah eksploitasi terhadap perempuan dan anak. Penelitian ini menggunakan metode kualitatif dengan sifat deskriptif-analitis untuk menggambarkan penerapan prinsip maslahat dalam pencatatan pernikahan dan relevansinya dalam pencegahan eksploitasi. Lokasi penelitian dipilih secara purposive karena tingginya kasus pernikahan tidak tercatat dan perkawinan anak di Kabupaten Mandailing Natal serta kuatnya pengaruh budaya lokal. Pendekatan normatif-empiris digunakan dengan mengintegrasikan analisis prinsip maslahat dalam hukum Islam dan realitas sosial masyarakat. Data primer dikumpulkan melalui wawancara mendalam dengan tokoh agama, tokoh masyarakat, dan warga terdampak menggunakan teknik purposive sampling, sementara data sekunder diperoleh dari literatur dan dokumen resmi. Pengumpulan data dilakukan melalui wawancara dan observasi, kemudian dianalisis secara kualitatif melalui reduksi data, penyajian data, dan penarikan kesimpulan, serta dilengkapi triangulasi sumber untuk menjamin keabsahan data. Hasil penelitian menunjukkan bahwa rendahnya kesadaran hukum, anggapan bahwa pencatatan hanya formalitas administratif, terbatasnya akses layanan, faktor ekonomi, dan maraknya perkawinan anak menjadi penyebab utama tingginya pernikahan tidak tercatat. Kebaruan penelitian ini terletak pada integrasi komprehensif antara prinsip maslahat dan temuan empiris lokal, menghasilkan rekomendasi kebijakan pencatatan pernikahan berbasis maslahat melalui edukasi hukum, perluasan akses layanan, dan inovasi digital sebagai langkah preventif melindungi perempuan dan anak.